2017
DOI: 10.1128/mcb.00611-16
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte-Derived Hsp90 Modulates Collagen Upregulation via Biphasic Activation of STAT-3 in Fibroblasts during Cardiac Hypertrophy

Abstract: Signal transducer and activator of transcription 3 (STAT-3)-mediated signaling in relation to upregulated collagen expression in fibroblasts during cardiac hypertrophy is well defined. Our recent findings have identified heat shock protein 90 (Hsp90) to be a critical modulator of fibrotic signaling in cardiac fibroblasts in this disease milieu. The present study was therefore intended to analyze the role of Hsp90 in the STAT-3-mediated collagen upregulation process. Our data revealed a significant difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 67 publications
0
68
0
Order By: Relevance
“…Hsp90 inhibition was found to reduce collagen I synthesis on hepatic stellate cells (HSCs) in liver fibrosis [8]. Interesting data described by different groups including ours, showed that pharmacological and biological inhibition of Hsp90 effectively blocks the pro-fibrotic effects of TGFβ in different preclinical models of skin fibrosis in systemic sclerosis [6], in cardiac hypertrophy [9] or in cardiac fibrosis [10]. Hsp90 was presented as a novel modulator of TGFβ signaling in lung adenocarcinoma and bronchoalveolar carcinoma cells [5].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Hsp90 inhibition was found to reduce collagen I synthesis on hepatic stellate cells (HSCs) in liver fibrosis [8]. Interesting data described by different groups including ours, showed that pharmacological and biological inhibition of Hsp90 effectively blocks the pro-fibrotic effects of TGFβ in different preclinical models of skin fibrosis in systemic sclerosis [6], in cardiac hypertrophy [9] or in cardiac fibrosis [10]. Hsp90 was presented as a novel modulator of TGFβ signaling in lung adenocarcinoma and bronchoalveolar carcinoma cells [5].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…72 Likewise, exosomes secreted from hypertrophied cardiomyocytes contain HSP90 and IL-6 (interleukin 6) to maintain STAT3 (signal transducer and activator of transcription 3)-fibrotic pathway signaling. 86 This study, however, also showed differential regulation of collagen expression in the cardiac fibroblast in vitro versus in vivo, which points toward the potential paracrine effects resulting from crosstalk among different cell types. It will be important for future studies to compare in vivo findings with in vitro systems to confirm which cell type is releasing exosomes to exert specific effects.…”
Section: Understanding the Paracrine Effects Exerted By Exosomes Secrmentioning
confidence: 65%
“…Cardiac fibroblast–derived exosomes enriched in miR‐21‐3p have been shown to be potential regulators of cardiomyocyte hypertrophy . Likewise, exosomes secreted from hypertrophied cardiomyocytes contain HSP90 and IL‐6 (interleukin 6) to maintain STAT3 (signal transducer and activator of transcription 3)–fibrotic pathway signaling . This study, however, also showed differential regulation of collagen expression in the cardiac fibroblast in vitro versus in vivo, which points toward the potential paracrine effects resulting from crosstalk among different cell types.…”
Section: Understanding the Paracrine Effects Exerted By Exosomes Secrmentioning
confidence: 70%
“…As TRITC and FITC work as a donor/acceptor in FRAP assay, TRITC was subjected to 50% bleaching, and FITC intensity in a single cell was measured. FRET efficiency was calculated from the difference between the postbleaching and prebleaching donor intensities (delta donor) using FV1200 confocal microscope (18).…”
Section: Frap Analysesmentioning
confidence: 99%
“…Data were analyzed by Student's ttest (comparison of two groups) and one-way analysis of variance followed by Tukey's test (comparison of multiple groups) using GraphPad Prism (Version 6.01; GraphPad Software, La Jolla, CA). Results with p-value <0.05 were considered significant (18,58).…”
Section: Statistical Analysesmentioning
confidence: 99%